Altered Fashions: Eighteenth-Century Quilted Petticoats in a Finnish Context - Shepherd, Anni (Edinburgh University Press, 2026)
Quilted petticoats were a common garment in the wardrobes of many women in eighteenth-century Finland. Both fashionable and practical, these items were passed on from one generation to the next and often altered and refashioned by their later owners. This article examines three such petticoats in the collections of the Porvoo Museum in Finland and places the garments within the sociocultural and historical contexts of their time. Through the study of these petticoats and the use of inventory deed records, this article discusses the value of textiles in eighteenth-century Finland and how such garments can be used as historical sources.